Characterization of Listeria monocytogenes strains isolated from soil under organic carrot farming - Nowak, Maciej; Paluszak, Zbigniew; Wiktorczyk-Kapischke, Natalia; Grudlewska-Buda, Katarzyna; Budzyńska, Anna; Skonieczna-Kurpiel, Joanna; Wałecka-Zacharska, Ewa; Huse-Kutowska, Monika; Skowron, Krzysztof (Frontiers in Microbiology, 2025)
IntroductionListeria monocytogenes are Gram-positive, non-spore-producing rods that are the etiological agent of listeriosis. L. monocytogenes is isolated from soil, water, sewage, rotting vegetation, and the main source of these rods for humans is food (fish, unpasteurized dairy products, or raw fruits and vegetables). In recent years, there has been an increase in consumer interest in healthy food, especially organically grown. The use of natural fertilizers during organic farming can be a source of pathogens, including L. monocytogenes in the soil and finally in vegetables and fruits. The aim of this study was to assess the prevalence of L. monocytogenes in soil samples from organic carrot crops (Poland) and to characterize the tested strains. Microbial contamination of the soil has a direct impact on the safety of the crops grown on it. This is an important aspect in organic farming, where products are chosen as a healthier option and consumed by children and the elderly.MethodsThe isolates were subjected to genetic similarity assessment (PFGE method), and the tested strains were evaluated for antibiotic susceptibility (disc-diffusion method), invasiveness (HT-29 line human colon cancer cell line), coaggregation with Salmonella Enteritidis, biofilm-forming ability and the effect of disinfectants on the biofilm.ResultsTwenty-seven isolates of L. monocytogenes were isolated from 250 soil samples, 10 of which were genetically different. 80% of the tested strains were sensitive to the tested antibiotics. Antibiotic resistance was demonstrated in two strains (strain 11 – resistant to penicillin and cotrimoxazole, strain 22 – resistant to penicillin). The highest invasiveness against HT-29 cells at 23.2% was shown for strain 11. However, invasiveness of less than 1% was demonstrated for three strains, and strain 13 showed no ability to invade HT-29 human colon cancer cells. The level of coaggregation between the tested strains and S. Enteritidis ranged from 22.2 to 39.1%. The number of biofilm-isolated rods from the stainless steel surface was 6.37 to 7.10 log colony-forming unit (CFU)/cm2, while on polypropylene it was from 6.75 to 8.06 log CFU/cm2. The effectiveness of the disinfectants used depended on the duration of action and the concentration of the disinfectant. Chlorosol was shown to be the disinfectant causing stronger biofilm eradication on each of the tested surfaces. It has been shown that soils and thus food from organic farming can be a source of L. monocytogenes. These rods can vary in phenotypic characteristics and virulence levels.DiscussionThe research conducted allows to draw attention to the occurrence of pathogens, including L. monocytogenes in crops from organic farming. In addition, the results presented can help to introduce standards regulating the safety of organic farming, taking into account the occurrence of antibiotic-resistant or highly invasive strains, thus maintaining food safety.